Environmental Impacts and Changes after the Eruption of Mount Kelud, Indonesia - Muhammad Agus Sirodj Haspan Bad; A Zahid (Jurnal Geografi, Lingkungan dan Kesehatan, 2026)
The 2014 eruption of Mount Kelud represents one of the most massive volcanic events in modern Indonesian history, causing severe bio-physical landscape destruction and subsequent reconstruction. This study aims to analyze the integration of bio-physical environmental changes with the socio-ecological dynamics of the communities surrounding Mount Kelud post-eruption, through the framework of Social-Ecological Systems (SES). The research examines the reciprocal interactions between bio-physical disturbances and community adaptive capacity, regime shifts in affected areas, and the effectiveness of community-based risk governance. A multidisciplinary approach was employed, integrating disaster geomorphology data with environmental sociology perspectives. Data were collected through direct field observations, field notes, and in-depth interviews with staff from the Kelud Volcanology Observatory and local community leaders. Findings indicate that the 2014 eruption surpassed critical bio-physical thresholds, leading to the destruction of previous geoheritage assets (such as the 2007 lava dome) and the formation of a new dynamic volcanic crater lake. In the long-term socio-ecological timeline, these disturbances triggered productive regime shifts. Local communities utilized Local Ecological Knowledge (LEK) to interpret pre-disaster natural cues, allow ecosystem recovery, and diversify livelihoods into pineapple cultivation and sand mining. Sociological resilience was further reinforced by the hybridization of LEK with digital Early Warning Systems (EWS) and strengthened local institutions through structured communal cooperation at neighborhood levels (RT/RW). The study concludes that post-eruption landscape management has successfully progressed toward a collaborative polycentric governance model, ensuring environmental resilience and sustainability for future generations.